Experience of a Personnel Manager Resolving Conflict in the Organization - Mačiulis, Šarūnas; Sondaitė, Jolanta (Socialiniai tyrimai, 2018)
This paper examines the experiences of personnel managers in Lithuania in solving conflict in the organization. The data were collected by means of a semi-structured interview. A thematic analysis was employed to achieve the goal. The results revealed three common themes: “conflicts caused by changes”, “conflict prevention”, “going through the conflict”. It was established that even though personnel managers use various strategies for avoiding conflict, they became involved, they experience strong negative emotional reactions.